Desmosine as a biomarker for the emergent properties of pulmonary emphysema - Cantor, Jerome (Frontiers in Medicine, 2023)
Developing an effective treatment for pulmonary emphysema will require a better understanding of the molecular changes responsible for distention and rupture of alveolar walls. A potentially useful approach to studying this process involves the concept of emergence in which interactions at different levels of scale induce a phase transition comprising a spontaneous reorganization of chemical and physical systems. Recent studies in our laboratory provide evidence of this phenomenon in pulmonary emphysema by relating the emergence of airspace enlargement to the release of elastin-specific desmosine and isodesmosine (DID) crosslinks from damaged elastic fibers.When the mean alveolar diameter exceeded 400 µm, the level of peptide-free DID in human lungs was greatly increased, reflecting rapid acceleration of elastin breakdown, alveolar wall rupture, and a phase transition to an active disease state that is less responsive to treatment. Based on this finding, it is hypothesized that free DID in urine and other body fluids may serve as a biomarker for early detection of airspace enlargement, thereby facilitating timely therapeutic intervention and reducing the risk of respiratory failure.